Efficiency of a predictive model for assessing the performance of the simple direct attack in terms of physical and motor abilities of junior fencers - Noor Hatem AlHaddad; Dhafer Namoos AlTaie; Mohammed Jasim Al-Yasiri (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.